IS HUBBLE BUBBLE SMOKING CORRELATED TO BONE MINERAL DENSITY OF POSTMENOPAUSAL WOMEN? - F. Gheidar; R. Jamshidi; A. NajafYarandi; Sh. Mokhtarshahi; E. Aflaky (Iran University of Medical Sciences, 2005)
Nowadays, parallel to the use of modern technology and various approaches in sanitation and medicine, life expectancy has raised dramatically. So, postmenopausal women can live longer, considering that, the osteoporosis is one of the menopausal complaints.   To determine the correlation between Hubble bubble smoking and bone mineral density of postmenopausal women we conducted a retrospective cohort study in which the bone mineral density of femur neck and lumbar spine of postmenopausal women was investigated. The interviews were done by phone for data gathering.   And 180 women were assigned in two groups of 60 smokers and 120 nonsmokers.   Finding revealed that despite the existence of difference between bone mineral density of Femur neck in smokers and nonsmokers (T=-1.988, P =0.048), variables of parity and level of education played important roles in the results. We also, found that the lumbar spine density was lower in smokers (T=-2.016, P =0.045) and after controlling of confounding variables, the difference was just related to Hubble bubble smoking (P=0.045).   It was concluded that education and parity had greater correlations with bone mineral density of femur neck. This can be due to paying more attention to sanitation among educated women. Also, there was a significant correlation between Hubble bubble smoking and bone mineral density of lumbar spine. Therefore, Hubble bubble smoking can be taken as one of the risk factors of low bone mineral density among postmenopausal women.